PENGARUH PEMBIAYAAN SYARIAH TERHADAP PERTUMBUHAN UMKM DI KECAMATAN PAUH KABUPATEN SAROLANGUN - Arya Ramadani; Ahsan Putra Hafiz (Fakultas EKonomi dan Bisnis Islam UIN Sulthan Thaha SAifuddin Jambi, 2026)
This study aims to comprehensively analyze the influence of Islamic financing on the growth of Micro, Small, and Medium Enterprises (MSMEs) in Pauh District, Sarolangun Regency, with a particular focus on financing provided by Bank Syariah Indonesia (BSI) Simpang III Branch. The research employed a quantitative approach by distributing questionnaires to 96 MSME actors as respondents, and the collected data were processed using simple linear regression analysis with SPSS software. The findings indicate that Islamic financing has a positive and significant effect on MSME growth, as evidenced by the regression coefficient value of 0.836, a significance level of less than 0.05, and a coefficient of determination (R²) of 0.787. This result implies that 78.7% of the variation in MSME growth is influenced by Islamic financing, while the remaining 21.3% is affected by other factors such as managerial quality, market conditions, innovation capacity, and human resource competence. Thus, the hypothesis (H1) is accepted, confirming that Islamic financing significantly contributes to the development and income improvement of MSMEs. Moreover, this finding strengthens the role of Bank Syariah Indonesia not only as a financial institution but also as an agent of community economic empowerment based on sharia principles, which emphasize justice, blessing, and balance in business activities.